Breast Tuberculosis after Chest Trauma - a Case Report and Review of the Literature - Perrone, Claudio (Breast Care (Basel), 2016)
BACKGROUND: Breast involvement of tuberculosis (TB) is well known but uncommon. It can resemble other diseases, including breast cancer, and diagnosis is quite difficult. So, when facing a breast lesion, a possible tubercular etiology should always be born in mind, relying on qualified laboratories to confirm the diagnosis. CASE REPORT: We describe a 42-year-old woman with a mammary fistula complicating a post-traumatic lump. A critical analysis of the diagnostic process was performed together with a review of the literature, also considering the potential role of trauma in inducing such a rare complication.